Biomechanical analysis of the horizontal jumping events at the 2009 IAAF World Championships in athletics - Mendoza, L.; Nixdorf, E. (New Studies in Athletics, 2011)
The 2009 IAAF World Championships in Athletics in Berlin presented German sport scientists with a rare opportunity to study the world`s best athletes in a top-level competition at a venue close to home. A team of 18 researchers from six institutions around the country planned, organised and carried out a major biomechanics research project at the championships with the support of the German athletic federation (DLV) and the IAAF.